A Qualitative Study Exploring Student Nurses’ Knowledge and Perceptions towards Entrepreneurship in Nursing - Halmshaw, Charlotte (2009)
This study aimed to explore the knowledge and perceptions of pre-registration student nurses towards nurse entrepreneurship. The objectives were to explore students’ knowledge, consider students’ attitudes and explore students’ beliefs of entrepreneurship. Current literature and health policies emphasise the need for an increased focus on nursing entrepreneurship due to the phenomenon of this subject becoming more important. The NHS and government are calling on nurses to become entrepreneurial. Despite this, very little is known about the knowledge and perceptions held by student nurses towards entrepreneurship. There is no qualitative research exploring student nurses’ perceptions towards nurse entrepreneurship in the UK. Participants for the research were selected from three pre-registration nursing courses at the local School of Nursing. The study adopted a qualitative approach using semi-structured interviews structured around the Benchmark Template (2006) and Bloom’s Taxonomy (2007). The data was analysed manually using an inductive approach, using theory and literature to interpret what the fifteen participants said.